PERANCANGAN SISTEM OTENTIKASI RADIUS PADA PENGGUNA JARINGAN WIRELESS UNTUK MENINGKATKAN KEAMANAN JARINGAN KOMPUTER - Darmadi, Eko Agus (IKRA-ITH INFORMATIKA : Jurnal Komputer dan Informatika, 2018)
One of the main changes in the telecommunications sector is the widespread use of wireless networks. The problem that will be faced when implementing a wireless network is the issue of security. If you want to design a wireless network, you must also design a security system like what you want to implement. Regarding the explanation above, an authentication system is established for wireless network users with Remote Authentication Dial-In User Service (RADIUS) technology that aims to authenticate, authorize, and centrally register user accounts in accessing the network. RADIUS works using a distributed client-server system with servers that implement the AAA protocol model (Authentication, Authorization, Accounting) to secure networks from unauthorized users. The authentication model used is PAP (Password Authentication Protocol) so that users can only enjoy the network when they have a username and password in the RADIUS server. RADIUS server supports multi-user and multi-roaming, this is expected to facilitate users when moving to each access point / network point without re-registering and can provide better security in a computer network.